2000
DOI: 10.1054/bjoc.2000.1119
|View full text |Cite
|
Sign up to set email alerts
|

Nested case–control study of the effects of non-steroidal anti-inflammatory drugs on breast cancer risk and stage

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) interfere with the growth of mammary tumours (Lala et al, 1997;Robertson et al, 1998) and prevent distant metastasis (Hubbard et al, 1988;Khoo et al, 1992) in rodents. The epidemiologic evidence for similar effects in women is limited and inconsistent (Isomäki et al, 1978;Friedman and Ury, 1980;Gridley et al, 1993;Thun et al, 1993;Schreinemachers and Everson, 1994;Harris et al, 1995Harris et al, , 1996Egan et al, 1996).To study the effects of NSAID use on breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 33 publications
2
105
1
1
Order By: Relevance
“…Nine studies evaluated dose-response relation of NSAID use and breast cancer but only two studies reported significant doseresponse relation for duration (Coogan et al, 1999) and frequency (Sharpe et al, 2000) of NSAID use. In one study (Coogan et al, 1999) the highest reduction in breast cancer risk was reported for the category 'unknown years of use'.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies evaluated dose-response relation of NSAID use and breast cancer but only two studies reported significant doseresponse relation for duration (Coogan et al, 1999) and frequency (Sharpe et al, 2000) of NSAID use. In one study (Coogan et al, 1999) the highest reduction in breast cancer risk was reported for the category 'unknown years of use'.…”
Section: Discussionmentioning
confidence: 99%
“…Although NSAIDs have been shown to reduce the risk of breast cancer (Sharpe et al, 2000), it is not known how they reduce this risk nor is it known what effect they have on established breast cancer. Both selective COX-2 (celecoxib) and non selective COX inhibition (ibuprofen) reduced the incidence and subsequent growth of primary breast tumours induced by 7,12-dimethylbenz(a)anthracene (DMBA) in female Sprague Dawley rats Harris et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies provided evidence of significant trend of risk reduction with increasing exposure to NSAIDs (Coogan et al, 1999;Sharpe et al, 2000), but there were insufficient data to estimate the overall combined dose -response effect for either duration or frequency of use in the meta-analysis.…”
Section: Epidemiology Of Cox Inhibitor Use and Breast Cancer Incidencementioning
confidence: 99%